Analisis Peran Kepala Sekolah dalam Mengembangkan Mutu Pendidikan Di SD Negeri 001 Bonai Darussalam Kabupaten Rokan Hulu - Lulu Lestari; Elpri Darta Putra (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This study aims to describe: the role of the principal in developing the quality of education, the supporting factors in developing the quality of education and the inhibiting factors in developing the quality of education at SD Negeri 001 Bonai Darussalam. This research was conducted at SD Negeri 001 Bonai Darussalam, Rokan Hulu Regency. This study uses a descriptive qualitative approach. The data sources of this research are the principal and 2 teachers. Data collection techniques and instruments in this case the researchers used the interview, observation and documentation methods. Focused data analysis using the Miles & Huberman model, namely data reduction, presentation and conclusion drawing. The findings of this study indicate that there are three roles of the principal in developing the quality of education at SD Negeri 001 Bonai Darussalam, namely the principal as a manager, the principal as an educator and the principal as a motivator. The supporting factors in developing the quality of education at SD Negeri 001 Bonai Darussalam are good human resources (HR), the existence of a teacher's jihad spirit in teaching and educating good students to make outstanding students, and the cohesiveness of school residents. . In addition, there are also inhibiting factors in developing the quality of education, namely the lack of infrastructure in the teaching and learning process, the competence of teachers who are still lacking in developing the quality of education at SD Negeri 001 Bonai Darussalam and environmental factors.